Analisis Dinamika Kepribadian Id, Ego, Superego Pada Tokoh Utama Cerita Pendek “rupanya aku bisa” Karya maria klavia.a - Very Angga Saputra; Muhammad Fatikhul Ikhwan; Eva Dwi Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is that the researcher wants to analyze more deeply the dynamics of the Id, Ego, Superego personality of the main character in the short story entitled